2007
DOI: 10.1007/s11240-007-9303-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and large scale application of cryopreservation techniques for shoot and somatic embryo cultures of tropical crops

Abstract: Shoot-tips and somatic embryos are the explants of choice for the in vitro long-term storage of ex situ plant genetic resources in liquid nitrogen. Cryopreservation of organized structures has significantly progressed, especially for species of tropical origin, with the development of several vitrificationbased procedures such as encapsulation-dehydration, vitrification and droplet-vitrification approaches. They have allowed improvements in survival and recovery after cryopreservation compared with conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(75 citation statements)
references
References 48 publications
1
65
0
9
Order By: Relevance
“…63 Plant in vitro cultures are also connected with plant ex situ conservation. 64 The protection of especially rare and endangered species can be done by the propagation of valuable plants, their introduction into botanic gardens, and then, if possible, to the natural sites. The method of artificial seeds in which fragments of parental plants are used can fulfill this role as well.…”
Section: Plant In Vitro Morphogenesismentioning
confidence: 99%
“…63 Plant in vitro cultures are also connected with plant ex situ conservation. 64 The protection of especially rare and endangered species can be done by the propagation of valuable plants, their introduction into botanic gardens, and then, if possible, to the natural sites. The method of artificial seeds in which fragments of parental plants are used can fulfill this role as well.…”
Section: Plant In Vitro Morphogenesismentioning
confidence: 99%
“…This approach can result in extreme rates of dehydration, which can cause cell volume reductions that are potentially lethal (Day et al, 2008). It has been suggested that slow-cooling is only suitable for non-organised tissues, as sufficient dehydration is more difficult to achieve in tissues with complex structures due to the different rates of water movement between and within plant cells with different characteristics (Gonzalez-Arnao et al, 2008).…”
Section: Slow Cooling or Controlled Rate Coolingmentioning
confidence: 99%
“…Vitrification involves the treatment of tissues in a mixture of highly concentrated penetrating and non-penetrating CPAs applied at non-freezing temperatures, followed by rapid cooling in LN (Gonzalez-Arnao et al, 2008;Panis & Lambardi, 2005). The combination of high intracellular solute concentrations (due to dehydration and some CPA penetration) and rapid cooling prevents the nucleation of water and the formation of ice crystals, both intracellularly and extracellularly, thus promoting the vitrification of water Mandumpal et al, 2011;Reinhoud et al, 2000).…”
Section: Vitrificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Brison et al (1997) demonstrated for the first time that cryopreservation can not only be used to conserve germplasm but also to eradicate viruses using the rootstock of Prunus infected with Plum Pox Potyvirus. Since then, cryogenic techniques have been successfully applied to a large number of plant species including agricultural and horticultural crops from temperate and tropical regions (Reed 2002;Panis and Lambardi 2006;Gonzalez-Arnao et al 2008). Moreover, cryotherapy involving vitrification of shoot tips does not require special equipment in addition to that used in a typical plant tissue culture laboratory.…”
mentioning
confidence: 99%